THE ROLE OF LINGUA-PRAGMATIC PRINCIPLES IN EXPRESSING AUTHOR’S INTENTION IN PUBLICISTIC TEXTS - Saidova Mamura Suleymanovna,; Rakhmanova Aziza Mansur qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article is devoted to the role of pragmatic principles in the expression and realization of the author’s communicative intention in publicistic texts. The research goal is to showcase the interdisciplinary nature of linguistics, specifically the connection between pragmatics and stylistics: observance of Cooperative maxims in newspaper articles, implication of politeness strategies to encode persuasive speeches. Analyzing the implied meaning through linguistic perspective help us decode the message more efficiently and accurately.